Respuesta :

Answer:

2

Step-by-step explanation:

Simplifying

4x + -4 = 2x + -2

Reorder the terms:

-4 + 4x = 2x + -2

Reorder the terms:

-4 + 4x = -2 + 2x

Solving

-4 + 4x = -2 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.

-4 + 4x + -2x = -2 + 2x + -2x

Combine like terms: 4x + -2x = 2x

-4 + 2x = -2 + 2x + -2x

Combine like terms: 2x + -2x = 0

-4 + 2x = -2 + 0

-4 + 2x = -2

Add '4' to each side of the equation.

-4 + 4 + 2x = -2 + 4

Combine like terms: -4 + 4 = 0

0 + 2x = -2 + 4

2x = -2 + 4

Combine like terms: -2 + 4 = 2

2x = 2

Divide each side by '2'.

x = 1

Simplifying

x = 1